Glucose-induced STUB1-GOT2 axis promotes aspartate synthesis and mitochondrial dysfunction in bladder cancer - Yunqiang Xiong; Qianxi Dong; Hongji Hu; Zhongqi Li; Xiangpeng Zhan; Fuchun Zheng; Hao Wan; Jiahao Liu; Shuyu Wu; Wang Pan; Ruize Yuan; Jing Xiong; et al. (Cell Death and Disease)
Abstract Aberrant glucose metabolism, a characteristic of malignant tumors, contributes to the development and progression of bladder cancer (BCa). However, the underlying mechanism by which aberrant glucose metabolism promotes BCa progression is still incompletely understood. Here, we demonstrate that low levels of STUB1 are associated with worse progression and poor prognosis of BCa patients. STUB1 overexpression attenuates BCa cell proliferation, migration and amino acid metabolism, especial aspartate metabolism. Mechanistically, we identify that STUB1 induces K6- and K48-linked polyubiquitination of GOT2 at K73 lysine residue to decrease its stability, which attenuates mitochondrial aspartate (Asp) synthesis and regulates mitochondrial dysfunction. GOT2 was significantly up-regulated in BCa tissues and negatively associated with STUB1 expression. Furthermore, we reveal that high glucose stress promotes Asp synthesis and tumor growth through STUB1-GOT2 axis. Collectively, our findings identify that STUB1-GOT2 axis is an important regulator for maintaining Asp synthesis and mitochondrial function in BCa cell growth, which highlights that targeting STUB1-GOT2 axis could be a valuable strategy to ameliorate BCa progression by inhibiting amino acid metabolic function.